The Implementation of Academic Word List and Its Implication to the Improvement of EFL Students’ Academic Writing Quality - Abdullah Syarofi; Shohiyah Shobaha (Lingua Cultura, 2023)
The research aimed to investigate the effectiveness or ineffectiveness in implementing an academic word list and its implication for improving English as a Foreign Language (EFL) students’ writing quality. Academic Word List (AWL) played an important role in expanding the student’s academic vocabulary knowledge. Basically, an academic word list was considered one of the effective ways to reduce students’ errors in writing. The research was proposed to review several related preceding studies, and the data found were described qualitatively. From the research conducted, it is found that fifteen out of eighteen studies (83,33%) confirm that the implementation of academic word lists provides a significant contribution to the improvement of students’ writing quality. On the other hand, three out of eighteen studies (16,67%) confirm that implementing an academic word list does not significantly contribute to improving students’ academic word knowledge. This may be attributable to the given portion of the academic word list utilized as supplementary material, and it can only be used outside the classroom without any teacher guidance. The result shows that implementing the academic word list may act as an effective/ineffective tool for improving students’ academic writing quality based on the portion and utilization of this tool in the course.